Sedum kuntsunianum (Crassulaceae: Sedoideae), a new species from southern Zhejiang, China - Jin, Shui-Hu; Zhou, Ying-Ying; Ding, Bing-Yang; Wang, Rong-Wei; Jin, Xiao-Feng (Phytotaxa, 2013)
Sedum kuntsunianum, a new species of Crassulaceae from Zhejiang, China, is described and illustrated. It is similar to S. makinoi in having opposite leaves that are obtuse at the leaf apex, and sepals and leaves that are spurred at the base, but differs in having a creeping habit, persistent decussate basal leaves (absent in S. makinoi), paired sterile stems in the axils of the basal leaves (absent in S. makinoi), sepals 5–9 mm long (2–3 mm in S. makinoi), and petals 7–8 mm long (4–5 mm in S. makinoi).